(untitled) (Bangladesh Journal of Livestock Research, 2016)
A feeding trial with 30 Pabna milking cows of 2 to 4 parities dividing equally into 5 groups was conducted to determine the effect of feeding protein from different sources on blood or milk urea nitrogen, and milk yield or protein content in native cows. Considering a group of cows fed a diet of rice straw and concentrate as the control (T0), two out of the rests were fed either with urea-molasses straw (UMS) (T1) or Matikalai (Vigna mungo) hay ( T2) as sources of basal roughage. The rest two groups of cows were fed the control diet replacing percent (%) of feed protein by the amount of urea and molasses fed to UMS group. The amount of urea and molasses was fed daily either in two meals (T3) or fed to cows mixing with other concentrate feed (T4). Feeding a basal diet of UMS, DS or leguminous hay did not affect milk protein (%) and daily milk production Feeding urea and molasses in meals or mix (T3 and T4) did not affect significantly (p>0.05) BSU and MUN contents. It indicates that feeding urea and molasses in two meals in a day either as a single mix of the two or as a mix of the two with concentrates significantly (p>0.05) reduced the concentration of BSU or MUN without having any change in milk protein (%) of the cows. Dry matter (DM) intake was significantly (p<0.05) higher in T1 treatment group followed by T4, T0, T3 and T2, respectively. Similarly, CP intake was significantly (p<0.05) higher in T1 and T2 treatment groups followed by T3 and T4 treatment groups. The values of CP intake were 490, 770, 760, 630 and 580 g/day for treatment groups T0, T1, T2, T3, and T4, respectively. Feedings urea and molasses as meals (T3) significantly (p<0.05) reduced the fat content in milk compared with other treatment groups. Similar to T3, UMS feeding also significantly (p<0.05) reduced fat content in milk compared to Matikalai hay and T4 treatment groups. Milk urea nitrogen (MUN) content in morning milk was lower compared to evening milk. These data showed that feeding urea or protein of organic sources had effect on BSU and MUN contents in the morning milk but had no significant effect on evening milk. The lower BSU or MUN content in milk of the cows fed urea and molasses either in daily meals or as mix with concentrates may be due mainly to a lower CP intake compared to UMS and Matikalai. Therefore, it may be concluded that feeding urea or organic protein had no significant effect on milk protein percent. Bangladesh J. of Livestock Res. 19(1-2): 85-96, Jan-Dec 2012